Pars plana vitrectomy with corneal transplantation – combined procedure - Szaflik, Jerzy; Kmera-Muszyńska, Maria; Wojnarowska, Małgorzata; Fryczkowski, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
The aim of our study is to present own observations with Eckardt temporary keratoprosthesis, during combined pars plana vitrectomy and corneal transplantation. We operated on two aphakic patients with unclear corneas and retinal detachment – I case, phtisis bulbi after recurrent uveitis – II case. Eckardt temporary keratoprosthesis was sutured to the corneal bed with 4 or 6 Ethilon 10,0 bites, pars plana vitrectomy was performed followed by corneal transplantation and silicone oil tamponade. We obtained good transplant clarity only in the I case, in the II case because of hipotony and persistent contact of silicone oil with cornea, transplant was cloudy and collapsed with small exception in the central area. After 3-rd month we noticed local retinal detachment in the periphery, which was supressed with laser photocoagulations. We think, that Eckardt temporary keratoprosthesis gives possibility to do vitrectomy in patients with unclear cornea, which was in the past impossible. However, combined procedure requires surgical skills in both: anterior and posterior segments of the eye.